Changes in pictorial construction and types of representation which formed the basis of modern art - Collins, Anne Marie (Rhodes University, Faculty of Humanities, Department of Fine Art, 1986)
The erosion of traditional French academic methods of picture-construction, and the eclipse of hierarchical subject-matter, ensured the emergence of a diversity of new painting styles in France by 1900 and the possibility of even more drastic departures from tradition in the 20th century, particularly in the work of Picasso, from 1900 to 1914.
Keywords: Picasso, Pablo, 1881-1973; Art, French -- 19th century; Art, French -- 20th century